2016
DOI: 10.1111/joes.12152
|View full text |Cite
|
Sign up to set email alerts
|

Overbidding and Heterogeneous Behavior in Contest Experiments: A Comment on the Endowment Effect

Abstract: Abstract. We revisit the meta-analysis of Sheremeta on overbidding in contest experiments and focus on the effect of endowment on overbidding. Sheremeta assumes, and finds evidence of, an increasing linear relationship between endowment and overbidding, Quantal Response Equilibrium (QRE) predicts an increasing concave relationship, while Baik and colleagues find an inverted Ushaped relationship in their analysis of a single experiment. We use the same data as in Sheremeta, but employ a different econometric mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Although a recession reduces global income and that can cause a higher level of conflict, it also reduces people's resources to be spent on conflict. Chowdhury and Moffatt (2017) and Baik, Chowdhury, and Ramalingam (2020) show that the availability of the conflict budget and the level of conflict has an inverted-U shaped relationship. Hence, it may be possible that when people with medium conflict budget hit with a COVID related recession, they end up with a low conflict budget and as a result engage less in conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recession reduces global income and that can cause a higher level of conflict, it also reduces people's resources to be spent on conflict. Chowdhury and Moffatt (2017) and Baik, Chowdhury, and Ramalingam (2020) show that the availability of the conflict budget and the level of conflict has an inverted-U shaped relationship. Hence, it may be possible that when people with medium conflict budget hit with a COVID related recession, they end up with a low conflict budget and as a result engage less in conflict.…”
Section: Discussionmentioning
confidence: 99%
“…The author pools experimental data from 30 studies, and runs a regression in which the overbidding rate is found to be positively related to the number of contestants and the relative (to the prize value) size of the endowment. Chowdhury and Moffatt (2017) add to the analysis of Sheremeta (2013), finding evidence for an inverted U-shaped relationship between relative endowment and overbidding. One notable null result in Sheremeta (2013) and Chowdhury and Moffatt (2017) is no effect of repetition in effort allocation, that is, both studies find that the overbidding rate is not different between one-shot and repeated experiments.…”
Section: Introductionmentioning
confidence: 90%
“…Chowdhury and Moffatt (2017) add to the analysis of Sheremeta (2013), finding evidence for an inverted U-shaped relationship between relative endowment and overbidding. One notable null result in Sheremeta (2013) and Chowdhury and Moffatt (2017) is no effect of repetition in effort allocation, that is, both studies find that the overbidding rate is not different between one-shot and repeated experiments.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Endowment effect has been successfully applied to various disciplines, namely, marketing (Janakiraman and Ordóñez, 2012; Janakiraman et al , 2016; Wang, 2009; Weaver and Frederick, 2012; Wood, 2001), economics (Chowdhury and Moffatt, 2017; Drouvelis and Sonnemans, 2017; Kahneman et al , 1991; Khalil and Wu, 2017; Knetsch, 1989; Knetsch and Sinden, 1984; Morrison and Oxoby, 2013), political science (Kahneman et al , 1990), behavioral economics (Dijk and Van Knippenberg, 1996; Nash and Rosenthal, 2014; Van Boven et al , 2000), experimental psychology (Hassall et al , 2016; Hood et al , 2016; Walasek et al , 2018) and law (Arlen and Tontrup, 2015; Korobkin, 2003).…”
Section: Theories and Propositionsmentioning
confidence: 99%